How risk signaling influences binge drinking impression formation: An evolutionary experimental approach - Boudesseul, Jordane (2021)
Background. Evolutionary theory-driven alcohol prevention programs for adolescents are lacking. This study introduced a binge drinking impression formation paradigm to test whether emphasizing sexual dysfunction induced by alcohol abuse lowers positive attitudes and expectancies related to binge drinking when compared with cognitive or long-term health consequences. Method. In a between-subjects experiment, 269 French high school students (age, M = 15.94, SD = 0.93, 63.20% women) watched professional-quality videos emphasizing sexual impotence (n = 60), cognitive impairment (n = 72), or long-term effects (cancer, cardiovascular disease, n = 68) induced by alcohol and then had to evaluate a drinking scene. We predicted that the video on impotence would be the most impactful when compared with the other videos. Results. Results showed that women evaluated the target as less attractive after viewing the cognitive video compared with the video on impotence. Men were more willing to play sports against the target after viewing the cognitive video, compared with the video on impotence. Conclusions. These results showed that evolutionary meaning might shape impressions formed by participants depending on the context. This study calls for further replications using the same design and materials.